Pengaruh Kelas Sosial dan Gaya Hidup terhadap Keputusan Pembelian Hijab Buttonscarves di Kota Banjarmasin - Emilia; Novia Nour Halisa; Nurul Wahyuni; Devi Rusvitawati (Smart Business Journal (SBJ), 2026)
This study aims to determine and examine the partial significant effect of social class on purchasing decisions of Buttonscarves Hijab in Banjarmasin City, to determine and examine the partial significant effect of lifestyle on purchasing decisions of Buttonscarves Hijab in Banjarmasin City, and determine and examine the simultaneous significant effect of social class and lifestyle on purchasing decisions of Buttonscarves Hijab in Banjarmasin City. The research employed a quantitative approach with an Explanatory Research design. The study was conducted in Banjarmasin City. The population consisted of consumers who had purchased and used Buttonscarves Hijab more than once within the last year. The sample size comprised 100 respondents selected using purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the assistance of SPSS version 23 software. The results showed that social class has a partially significant effect on purchasing decisions of Buttonscarves Hijab in Banjarmasin City. Lifestyle also has a partially significant effect on purchasing decisions of Buttonscarves Hijab in Banjarmasin City. Furthermore, social class and lifestyle simultaneously have a significant effect on purchasing decisions of Buttonscarves Hijab in Banjarmasin City. Keywords: Social Class, Lifestyle, Purchasing Decision